Family financial management: organizing the financial aspects of the family-based on Maqasid al-Shariah - Mohammad Shihan, Mohammad; Zaroum, AbdulHamid Mohamed Ali (Contemporary Fiqh Research Unit (CFRU) & Islamic Book Ttust Kuala Lumpur, 2021)
Islamic Shariah pays higher attention to the preservation of the family institution. Hence, the financial stability of the family is considered a significant way of its preservation because, the finance of a family relates to all other elements such as education, security, health, and prosperous life. Therefore, the lack of knowledge about managing financial activities leads to many disorders and problems in the family. Accordingly, experts have found that financial management means planning, organize, prioritize, control and monitor financial activities to enhance the life of the family members with all the above-mentioned dimensions. Indeed, Islamic Shariah highly promotes that each activity of human beings should be planned and organized. Further, wealth is a trust on the shoulders of a Muslim, and he/she is accountable for its accumulation and distribution on the day of judgment. So, the need of having a proper management system for financial endeavors in line with Shariah principles is highly acknowledged. Nonetheless, Shariah scholars have paid less attention to this vital subject. Thus, understanding of the Islamic perspective of wealth is considered foremost important to organize the financial activities of the family. Hence, to organize the financial conduct the researcher has proposed some notions such as Maqasid based on the order of importance namely essential, exigencies and enhancements and, the notions such as prioritization, consequentialism, moderation and ‘Shura’ consultation. Hence, following the qualitative method to develop this paper the researcher depends on the available religious texts, publications, and articles related to the higher objective of Shariah. Therefore, this paper aims to propose some ideas to organize the financial activities of the family to avoid financial harm and disorders while enhancing the quality of life.